ANALISIS KETERAMPILAN BERPIKIR KREATIF SISWA DALAM PEMECAHAN MASALAH ENERGI ALTERNATIF - Ayu Maulidiah, Dina; Dwi Yasa, Arnelia; Nur Kumala, Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students' cr’ative thinking skills In solving alternative energy problems. However, science and science learning in elementary schools, particularly in the alternative energy topic, tends to be teacher-centered and emphasizes memorization of concepts, thus not encouraging students to think creatively and contextually. This situation Is not fully aligned with the spirit of ’he Independent Curriculum, which emphasizes deep learning. This study aims to analyze elementary school students' creative thinking skills In solving alternative energy problems In science and science learning. The study used a descriptive qualitative approach to describe students’ creative thinking processes based on Indicators of fluency, flexibility, originality, and elaboration. The results are expected to provide an In-depth picture of the dynamics of students' creative thinking and serve as a basis for each’rs in designing science and science learning that is more innovative, meaningful, and relevant to everyday life.